The Role of the Karang Tengah Police in Creating Public Order through a Comprehensive Approach - Lalu Hedwin Hanggara; Azis Budianto (Green Publisher, 2022)
Because a developing country, Indonesia is trying to keep up with the increasingly rapid technological developments. Originally it was estimated that with the development of the times, crime rates would be suppressed and crimes could be crushed because human thought was growing. But in fact, the times have contributed to increasing the quantity of crime in Indonesia, both fraud, defamation through social media, gambling and so on. One of the disputes that often occurs within the Karang Tengah Demak Polsek is the rise of fights between village youths due to a wrong use of social media which leads to fights. The approach used in this study is the sociological juridical method in connection with the role of bhabinkamtibmas in supporting security and public order. The results in this study are that the Karang Tengah Polsek in the context of maintaining community security and law enforcement based on Article 14 of Law Number 2 of 2002 concerning the National Police, namely: 1) carrying out arrangements, guarding, escorting and patrolling community and government activities as needed; 2) organize all activities to ensure security, order and smooth traffic on the road; 3) fostering the community to increase community participation, awareness of community law and adherence of community members to laws and statutory regulations; 4) participate in fostering national law; 5) maintain order and guarantee public security.